2004
DOI: 10.1080/16226510490439918
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Inoculation—Perspectives in Tailings Phytostabilization

Abstract: Intensive mining and processing activities worldwide resulted in the generation of huge amounts of waste (tailings), generally characterized as toxic, radioactive, and/or hazardous. The exposure potential and, hence, the risk posed by such wastes is enhanced by a general lack of vegetation. Phytostabilization has proven to be efficient in reducing this risk. However, establishing vegetation on tailing dumps may be expensive due to the intensive use of amendments and chemical fertilizers. In this article, inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 12 publications
1
33
1
Order By: Relevance
“…Abandoned tailing storage facilities (TSFs), for instance, are a potential source of pollution given their high metal concentrations (Badilla-Ohlbaum et al 2001, Frérot et al 2006, Ginocchio et al 2006. Loose tailings particulate matter is easily mobilized by wind, rain, and landslides, altering stream and soil quality, thus posing risks for crops, animal husbandry, wildlife, and human health (Petrisor et al 2004, Mendez & Maier 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Abandoned tailing storage facilities (TSFs), for instance, are a potential source of pollution given their high metal concentrations (Badilla-Ohlbaum et al 2001, Frérot et al 2006, Ginocchio et al 2006. Loose tailings particulate matter is easily mobilized by wind, rain, and landslides, altering stream and soil quality, thus posing risks for crops, animal husbandry, wildlife, and human health (Petrisor et al 2004, Mendez & Maier 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The value of DHA might be small if sufficient substrate does not exist. Petrisor et al (2004) reported that the DHA value with a glucose substrate could be ten times larger than the value without glucose. Furthermore, not all enzymes are synthesized by a cell in the same amounts; some enzymes are present in far greater number than others (Maila and Cloete 2005).…”
Section: Soil Dhamentioning
confidence: 97%
“…Unlike other existing methods, phytostabilization may be applied over larger areas and presents a favorable cost-benefi t ratio. This ratio may be further improved by using metallophyte plants with other uses (added value), which could also benefi t the economic development of local communities (Ginocchio, 2004;Petrisor et al, 2004;SONAMI, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among the emerging technologies for the rehabilitation of degraded areas, phytostabilization has proven to be an effi cient, environmentally appropriate and relatively low cost approach (Berti and Cunningham, 2000;Petrisor et al, 2004). In relation to mining wastes, phytostabilization consists of setting out metallophyte plants, applying appropriate substrate amendments.…”
Section: Introductionmentioning
confidence: 99%